KICT walk 2023: recharge and reconnect - Ismail, Ahsiah; Ahmad Puzi, Asmarani; Abdul Rahim, Elin Eliana; Basri, Atikah Balqis (KICT, IIUM, 2023)
KICT Sejahtera organised a KICT WALK on the 23rd of June 2023. The Staff members from Kulliyyah of Information and Communication Technology (KICT) and IIUM Academy of Graduate and Professional Studies participated, with a total of 27 participants joining the event.